Screening for ADHD Among Offenders of Intimate Partner Violence. Issue 3 (2nd July 2016) - Buitelaar, Nannet J.L.; Ferdinand, Robert F.; Posthumus, Jocelyne A.; Buitelaar, Jan K.
ABSTRACT: Since Attention-Deficit/Hyperactivity Disorder (ADHD) is presumed to be a risk factor for intimate partner violence (IPV) it is important to screen for the presence of ADHD in this population. Screening instruments for ADHD however have not been tested for use in forensic psychiatry. The aim of the present study was to assess the screening capacity of the Adult ADHD Self-Report Scale-Version 1.1 (ASRS-V 1.1), the ultra short questionnaire for ADHD (UKV) and the ADHD DSM-IV Rating Scale for adults (ADHD RS) among offenders of IPV in forensic psychiatry. One hundred and fifty participants, all of them outpatients of a forensic mental health service and referred for IPV, filled in the screeners upon intake and were subsequently assessed with the structured diagnostic interview for ADHD in adults 2.0 (DIVA 2.0). Diagnostic accuracy was moderate for ASRS-V 1.1 (AUC = .85; 95% CI = .79–.91) and UKV (AUC = .81; 95% CI = .74–.88) and high for ADHD RS (AUC = .94; 95% CI = .90–.97). Screening capacities were moderate for ASRS-V 1.1 (PPV = .81; 95% CI = .71−.88) and UKV (PPV = .78; 95% CI = .67–.85) and very good for ADHD RS (PPV = .90; 95% CI = .81–.95).